2022
DOI: 10.1101/2022.09.29.510105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-335-5p suppresses voltage-gated sodium channel expression and may be a target for seizure control

Abstract: There remains an urgent need for new therapies for drug-resistant epilepsy (DRE). Sodium channel blockers are effective for seizure control in common forms of epilepsy, but loss of sodium channel function underlies some genetic forms of epilepsy. Approaches that provide bi-directional control of sodium channel expression are needed. MicroRNAs (miRNA) are small non-coding RNAs which negatively regulate gene expression. Here, we show that genome-wide miRNA screening of hippocampal tissue from a rat epilepsy mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…As miR-324-5p represses the expression of Kcnd2, it follows that antisense inhibition of miR-324-5p leads to increased Kv4.2 functional expression and a reduction in neuronal excitability and seizures (Gross et al, 2016;Tiwari et al, 2019). Similarly, a recent study showed that miR-335-5p is able to reduce susceptibility to induced seizures via repression of the voltage-gated sodium channel subunit Scn2a (Heiland et al, 2022).…”
Section: Microrna Interactions With Ion Channelsmentioning
confidence: 96%
See 2 more Smart Citations
“…As miR-324-5p represses the expression of Kcnd2, it follows that antisense inhibition of miR-324-5p leads to increased Kv4.2 functional expression and a reduction in neuronal excitability and seizures (Gross et al, 2016;Tiwari et al, 2019). Similarly, a recent study showed that miR-335-5p is able to reduce susceptibility to induced seizures via repression of the voltage-gated sodium channel subunit Scn2a (Heiland et al, 2022).…”
Section: Microrna Interactions With Ion Channelsmentioning
confidence: 96%
“…It is possible that the impact of species‐specific sequences may be mitigated by the ability of miRNAs to operate with only partial target complementarity, adding complexity to the translation of studies between animal models and the human brain. To overcome this, studies in the epilepsy field have used surgically resected specimens in order to characterise MTIs in the human seizure focus (Heiland et al., 2022). A recent method (Morris et al., 2022) allows for the application of antimiRs to non‐diseased acutely resected human temporal neocortex (note – this tissue was removed during resective epilepsy surgery to give access to the seizure focus within the temporal lobe; whilst the neocortical tissue is assumed healthy, it was taken from the brain of a person with epilepsy and should be interpreted in this context).…”
Section: Microrna Properties Biogenesis and General Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study by Heiland and colleagues identified miRNA-335-5p as a potential target for modulating VGSCs in a combination of animal and human epilepsy models. 6 Previous reports that aimed to identify miRNAs that were altered in treatment-resistant forms of epilepsy were based on datasets from only rodent models or a single tissue type, which might limit clinical relevance. In contrast, Heiland et al, explored miRNAs that emerged from multiple datasets, including both rodent tissue and human biofluids, to increase the potential of identifying miRNAs that might be common to multiple forms of treatment-resistant epilepsy.…”
Section: Commentarymentioning
confidence: 99%
“…In contrast, Heiland et al, explored miRNAs that emerged from multiple datasets, including both rodent tissue and human biofluids, to increase the potential of identifying miRNAs that might be common to multiple forms of treatment-resistant epilepsy. 6 The expression datasets that were used were derived from a perforant path stimulation rat model of temporal lobe epilepsy, blood samples from patients with epilepsy, and mouse brain following treatment with cannabidiol (CBD). Out of over 200 candidates, a single miRNA, miR-335-5p, was found to be altered in all 3 datasets, and importantly, the sequence of miR-335-5p is conserved between rodents and humans, highlighting the potential translational relevance of miR-335-5p.…”
Section: Commentarymentioning
confidence: 99%